Designing and Characterization of a Novel Delivery System for Improved Cellular Uptake by Brain Using Dendronised Apo-E-Derived Peptide - Al-azzawi, Shafq; Masheta, Dhafir; Guildford, Anna; Phillips, Gary; Santin, Matteo (Frontiers in Bioengineering and Biotechnology, 2019)
Neurodegenerative diseases (ND) are characterised by the progressive loss of neuronal structure or function mostly associated with neuronal death. The presence of the blood–brain barrier (BBB) is considered the main obstacle that prevents the penetration of almost all drugs rendering the diseases untreatable. Currently, one of the most promising approaches for drug delivery to the brain is by employing endogenous transcytosis to improve endothelial cell uptake. This study aimed to exploit this potential route of enhanced drug uptake through the design and characterisation of low generations lysine dendrons with further functionalisation of dendron with ApoE-derived peptide (AEP) ligand to improve cellular uptake and targeting of delivery to the brain. Dendrons and peptide were synthesised using solid phase peptide chemistry and the products were characterised by mass spectrometry and high performance liquid chromatography which confirmed the successful synthesis of dendrons and functionalisation with the AEP. Cell viability and lactate dehydrogenase release were conducted to study the cytotoxicity of the materials against an immortalised brain endothelial cell line (bEnd.3) which demonstrated that no toxicity was seen at the concentration range used (up to 400 µM) for up to 48 h incubation. Cellular uptake of the synthesised molecules was examined using confocal microscopy and flow cytometer which clearly showed the cellular uptake of the dendronised carrier systems and that the highest percentage of cellular uptake was achieved with the AEP-functionalised dendron. This study has therefore demonstrated the successful synthesis of dendronised carrier systems with the potential to act as carriers for improved delivery and targeting the brain.